Kerusakan Alam dan Mitigasi Krisis Lingkungan (Kajian Surat Al-Baqarah Ayat 205-207 dalam Tafsir Al-Maraghi) - Al Hazmi, Muhammad Anas; Nur Azizah, Fina Haifa; Hajar, Siti; Ahmad, Hanif Jamaludin; Al Abrar, Muhammad Raif (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2024)
Environmental damage is a global issue that is increasingly urgent to address. In this context, understanding the views of the Qur'an and its commentaries on natural damage provides an important spiritual and ethical foundation in protecting the earth as a mandate from Allah SWT.  This study aims to analyze the views of the Qur'an and Tafsir al-Maraghi on natural damage, as well as identify mitigation efforts that can be taken to overcome the environmental crisis. The research method used is content analysis of Qur'anic verses related to the environment and Al-Maraghi's interpretation. Primary data was obtained from Tafsir al-Maraghi by Ahmad Mustafa al-Maraghi, while secondary data involved literature related to environmental damage. From the content analysis, it was found that the Qur'an provides a clear message about human responsibility in protecting the environment. Tafsir Al-Maraghi provides an in-depth understanding of the concept of ecology in Islam and the importance of maintaining the balance of nature. By understanding the views of the Qur'an and its commentaries, humans are reminded of their responsibility as caliphs on earth to protect and preserve the environment. Efforts made against the environmental crisis must be based on three mitigations; ecosystem care, sustainable management, and compliance with regulations.